Lócus de controle e conceito de maternidade e paternidade em adolescentes - Braga, Liliane Pereira (2012)
Locus of control is a construct that seeks to explain people's perceptions about the source of control of events, if the subject's own - internal - or belonging to some element outside of oneself - external. The location of individual s locus of control will suffer influence of their developmental period. During adolescence, individuals turn to the construction of their identity, and the structuring of sexual identity is a relevant part of this process, since the roles of males and females are the most important from the socio-cultural point of view. One of the roles that adolescents can take is the mother or father. We chose to head the adolescents who are not mothers and fathers, and question them about their concepts of parenthood. It is hypothesized that adolescents with internal locus of control will probably develop concepts of maternity and paternity in which they attach to themselves the responsibility for children. The aim of this study was to relate the locus of control s predominant dimension in adolescence and the way that these young people conceptualize parenthood. This is an exploratory analytical cross-sectional study accomplished with 400 adolescents from the classes of the sixth to ninth grade of high school at public schools in Natal / RN. We used as protocols: structured questionnaire involving sociodemographic questions and questions about the concept of parenthood, and the Multifactorial Scale of Locus of Control. Data were analyzed using descriptive and inferential statistics, with the aid of statistical package SPSS 18.0. The results regarding questions about the concept of maternity and paternity were analyzed using the analysis program often ALCESTE 4.7. The results showed that for boys and girls, maternity and paternity were characterized by the acquisition and assumption of responsibilities of adulthood. This concept is supported by the locus of control s classification of individuals, since most of the subjects of this study was characterized as individuals who tend to take responsibility for their life's events. For young people from lower classes (as the subjects of this research), the project of autonomy and social mobility is realized by the constitution of his own family and the ability to sustain it